Analysis of Age and Gravidity Factors with the Occurrence of Prolonged Parturition in the Midwifery Room of the Viqueque City District Hospital, Timor-Leste - Natalina Soares Almeida; Agusta Dian Ellina; Wahyu Purnomo Jati; Endra Widiyanto (Universitas STRADA Indonesia, 2024)
Prolonged or obstructed labor constitutes 8% of the causes of maternal mortality globally and is also the cause of fetal death. One of the causes of prolonged labor is maternal age and gravidity. The purpose of this study was to analyze the factors of age and adolescence with the incidence of prolonged labor in the midwifery room of the Viqueque City Hospital, Tomor Leste.This study used an analytical research design with a cross sectional approach. The population was all women who gave birth for a long time in the midwifery room of the Viqueque City Hospital, Timor Leste, which could be 30 people. The sampling technique used accidental sampling. The research instrument used a questionnaire and observation sheet. The data analysis used Chi Square statistical test.The results showed that more than half of the respondents (66.7%) aged 20-35 years were 20 respondents and more than half (53.3%) were multigravidas as many as 16 respondents, more than half (60%) did not occur during prolonged labor, namely as many as 18 respondents.Based on the results of statistical tests using Chi Square calculations, it is not known that no one knows it is 0.002 <0.05 so it can be shown that there is a relationship between the incidence of prolonged labor.Women with higher parity are at higher risk of prolonged labor because the uterus has weakened the uterine wall muscles due to a previous pregnancy. The solution that needs to be done regarding the results of the above research is to enable health education about the causes and risk factors for the old party to the mother by health workers and early detection of risk factors for prolonged labor must be improved.